Estradiol treatment in young postmenopausal women with self‐reported cognitive complaints: Effects on cholinergic‐mediated cognitive performance. (24th February 2022) - Conley, Alexander C.; Albert, Kimberly M.; McDonald, Brenna C.; Saykin, Andrew J.; Dumas, Julie A.; Newhouse, Paul A.
Abstract: Objective: Older women are at increased risk of developing Alzheimer's disease compared to men. One proposed reason is that following menopause there is a decline in estrogens. Estrogens are important for cholinergic functioning and attenuate the impact of cholinergic antagonists on cognitive performance in postmenopausal women. Self‐reported or subjective cognitive complaints in middle or older age may represent a harbinger of cognitive decline and those who endorse cognitive complaints appear more likely to develop future cognitive impairment. However, the response of individuals with cognitive complaints after menopause to estrogen and the relationship to cholinergic functioning has not been investigated. This study investigated the effect of estrogen treatment using 17β‐estradiol on cognitive performance following anticholinergic blockade in postmenopausal women and the relationship of this interaction with the level of self‐reported (subjective) postmenopausal cognitive complaints. Methods: Forty postmenopausal women (aged 50–60 years) completed a 3‐month treatment regimen of either 1 mg oral estradiol or placebo. Participants then completed four challenge days in which they completed cognitive and behavioral tasks after one of four cholinergic antagonist drug conditions (oral mecamylamine (MECA), intravenous scopolamine, combined MECA and scopolamine, or PLC). Results: Compared to PLC, the estradiol treated group performed worse on attention tasks under cholinergic challenge including the choice reaction time task and the critical flicker fusion task. In addition, participants who endorsed greater cognitive complaints showed reduced performance on the N‐back working memory task, regardless of whether they received estradiol treatment. Conclusions: The findings of this study indicate that estradiol treatment was unable to mitigate anticholinergic blockade in postmenopausal women with subjective cognitive complaints, and worsened performance on attention tasks. Moreover, the present study suggests that greater levels of cognitive complaints following menopause may be associated with an underlying decline in cholinergic function that may manifest as an inability to compensate during working memory tasks.